Dimensions of ideal leadership: Prophet Muhammad (P) as the greatest leader - Haque, A. K. M. Ahasanul (2014)
The purpose of this paper is to articulate the idyllic leadership qualities of Prophet Muhammad (P) from the fundamental sources of Islam- “Al-Quran” and “Hadith” in order to build a role model for conventional leaders of management science where the traditional attributes of a leader and the absence of negative features are included for arguments. There are some distinguishing traits of the Prophet which are essential for any leader to be triumphant in the field of management. Here, the authors have elucidated those qualities in order to fabricate a model so that it can be executed in the practice of management. A conceptual style is used to document the leadership characteristics of the Prophet. It is based on the basic books of Islam like “Al- Quran” and “Hadith”. To discuss traditional leadership, some previous research papers are also comprised as immense source of management principles and actions. All the short-comings and drawbacks can be overcome by adopting the inclusive and supreme qualities of Prophet Muhammad (P) as Islam is the complete code of life and management is not an exception. And the best living illustration of Islam is the Prophet Muhammad (P). If management leaders can assume the traits of the Prophet then the basic problems of leadership like the clash between Individualism and collectivism can be resolved beside all other predicaments. There are several researches which have included the same type of subject matter but in this paper a model has been developed where the outstanding qualities of the Prophet are included and the fundamental attributes of an ideal leader are also included. Beside that the absence of negative traits are also given importance. Keywords Muhammad, Leadership, Qualities, Model, Islam Paper type Conceptual paper